Photoreactive polymer and C,H-insertion reaction to tailor the properties of CHA/gelatin-based scaffold - Ardhani, Retno; Suraya, Tiyastiti; Wulanjati, Martha Purnami; Ana, Ika Dewi; Rühe, Jürgen; Pidhatika, Bidhari (Taylor and Francis, 2022)
A series of photoreactive polymers containing poly(N,N-dimethylacrylamide) and 2-hydroxy-(4-methacryloyloxybenzophenone), P(DMAA-n%MABP-OH), was explored to modify sheet-formed carbonated hydroxyapatite/gelatin (CHA/gelatin) scaffold. Under UV-light illumination, the benzophenones react with any C–H bonds in their vicinity through a C,H-insertion mechanism, enabling PDMAA-based hydrogel formation that is covalently attached to the gelatin. NMR spectroscopy confirmed the chemical structure of P(DMAA-n%MABP-OH) polymers with aimed n = 1, 5, 10, while GPC determined their molecular masses. The benzophenone reactivity under UV-light illumination for 0–240 min. was demonstrated using UV-Vis spectroscopy at 240–400 nm. After immobilization of P(DMAA-n%MABP-OH) onto the CHA/gelatin scaffold, typical FTIR vibration bands of both compounds could be detected on the spectra of the modified scaffolds. SEM images showed that the scaffold is highly porous with approximately 100 µm thickness. P(DMAA-n%MABP-OH) addition led to 2–3 times increase in thickness and 15–19% mass addition. Furthermore, it was shown that chemical (degradation and Ca2+ release profile), physical (4−7 swelling index), mechanical (0.06−0.17 MPa wet tensile strength and 0.2−0.8 MPa elastic modulus), and biological (cell adhesion) properties of the scaffold could be tailored by varying the photocrosslinker content. Cytotoxicity test showed that all studied CHA/gelatin-based scaffolds were nontoxic (>80% cell viability).